Perkawinan Usia Muda dan Pengaruhnya terhadap Angka Perceraian: - Husna Sari Siregar; Aji Pratama; M. Sukron Siregar; Nur Sakinah Hasibuan; Winda Fauzia Harahap (Fakultas Syariah IAIN Laa Roiba Bogor, 2024)
Marriage is a means to create a new household or family between a man and a woman. Through this research, we want to know and find cases where divorce occurs because of early marriage. 1 This research is a qualitative research. 1). Marriage is everyone's right and he has the right to live it. Where at this age there are many challenges in life. 2) Early childhood is called the golden age, where children easily receive stimulation, both directly and indirectly, as well as various educational activities from their environment. The consequences of early divorce are internal and external factors. Internal factors include disputes, cost issues and affairs. External factors are factors of understanding religion, economy and cultural customs. 2 Development of young couples is very necessary, because they still have developmental tasks in the search for identity and social identity which are sometimes still confusing. One focus of their training and counseling is social maturation. Keywords: marriage, early age, divorce